Engineering modeling and design - William Luther Chapman (CRC Press, 1992)
The book presents fundamental principles for designing effective systems. It shows examples for this systems design approach. It also presents other system design tools, such as the Japanese quality function deployment (QFD), integrated definition (IDEF), design for manufacturability, and concurrent engineering, that are often used in the system design process